(untitled) (International Journal of Nursing Education, 2022)
Backgrounds: The increasing number of COVID-19 cases demands the preparedness of nurses as the front line in providing health services to prevent being infected with COVID-19. This non-natural disaster has been declared a pandemic epidemic in the world so that efforts must be made to overcome it Objectives: The purpose of this study was to determine the factors that influence the management of preparedness and nurse response to COVID-19 prevention measures in a government-owned public hospital in a province in Indonesia. Methods: This quantitative study used a correlative design with a cross sectional approach to 220 nurses who were selected using a proportionate stratified random sampling technique. The data were obtained using a selfreport questionnaire and analyzed using the Chi-Square test and Logistic Regression. Results: The results showed that the effective response factor and facility readiness were the factors that most influenced the nurse’s preparedness and response to COVID-19 prevention measures in hospitals. Nurses are expected can maintain their already very good preparedness so that no more nurses are infected with the COVID-19 virus and are ready to be on standby with a new variant of the virus. Hospitals are expected to carry out routine maintenance of facilities so that preventive measures for COVID-19 nurses can be carried out effectively and appropriately and with adequate facilities and infrastructure.